CD56bright NK cells are enriched at inflammatory sites and can engage with monocytes in a reciprocal program of activation. - Dalbeth, N; Gundle, R; Davies, R; Lee, Y; Mcmichael, A; Callan, M (2004)
Human NK cells may be divided into a CD56(dim) subset and a CD56(bright) subset. In peripheral blood, CD56(dim) NK cells dominate, whereas in lymph nodes, CD56(bright) NK cells are more common. In this study we show that CD56(bright) NK cells accumulate within inflammatory lesions in a wide variety of clinical diseases affecting several different anatomical sites. We demonstrate that when activated by the monokines IL-12, IL-15, and IL-18, these NK cells promote TNF-alpha production by CD14(+) monocytes in a manner that is dependent on cell:cell contact. Conversely, CD14(+) monocytes synergize with monokines to promote IFN-gamma production by these NK cells. Again, this interaction is dependent on cell:cell contact. The experiments show that CD56(bright) NK cells accumulate in inflammatory lesions and, in the appropriate cytokine environment, can engage with CD14(+) monocytes in a reciprocal activatory fashion, thereby amplifying the inflammatory response. Such a positive feedback loop is likely to be important in the pathogenesis of chronic inflammatory conditions such as rheumatoid arthritis.